Harvesting Operations in the Tropics - Sessions, John.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
The book brings together information on harvest methods, system productivity, and methods for conducting safe, efficient, and environmentally acceptable operations in tropical forests. It highlights the challenges of harvest operations in the tropics, includes techniques that have been shown to be successful, and discusses newer technologies. The book is a reference for those interested in planning and management of tropical forests. Numerical examples are provided to provide clarity for interpreting graphs, procedures, and formulas. The book covers harvest systems from planning for felling to log transport from the forest, and concludes with considerations in selecting the appropriate harvesting technology.
Planning -- Organization, Administration, and Labor Productivity -- Felling -- Animal Skidding -- Ground-Based Mechanized Skidding and Forwarding -- Cable and Helicopter Yarding Systems -- Loading -- Transport -- Appropriate Harvesting Technology -- Concluding Comments.
Keywords: Forestry management; Forestry; Forest products; Agriculture; Environmental management; Forestry Management; Forestry; Wood Science & Technology; Agriculture; Environmental Management